Scientific American. – 1867. – Vol. 17, № 12 - б/а (New York. Munn & Company, 1867)
A weekly journal of practical information, art, science, mechanics, chemistry and manufactures.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; Research Subject Categories::NATURAL SCIENCES; Research Subject Categories::TECHNOLOGY; September 21, 1867